PENDAMPINGAN KELUARGA TERHADAP PENDERITA HIPERTENSI DALAM MENGENDALIKAN HIPERTENSI MELALUI MANAJEMEN DIET DASH (DIETERY APPROACH STOP HYPERTENSOIN) - Rozikhan Rozikhan; Sri Setiasih; Supardi Supardi (PT.Mantaya Idea Batara, 2024)
Hypertension as a public health problem and identified as a major risk factor for morbidity and mortality of cardiovascular diseases, especially stroke and chronic kidney disease and becomes an economic and social burden. One of the efforts to regulate diet patterns is very important in fulfilling nutrition as a hypertension controller. Lifestyle changes as one of the management of hypertension, therefore it is necessary to make efforts to help control hypertension by choosing a DASH (Dietary Approaches to Stop Hypertension) diet pattern. This study was to determine changes in systolic and diastolic blood pressure in hypertension patients after implementing the DASH diet. The results of this study are expected to be used as a guideline for how important it is that the DASH diet is an effective action in controlling blood pressure in hypertension patients. The study used a quasi-experimental study with a pre-post study, namely providing education to hypertension patients and family members as companions using a leaflet model containing the DASH diet. The assessment was carried out after the first 6 days and the second 6 days to determine changes in blood pressure using a tensiometer. The results of the study showed a decrease in systolic and diastolic blood pressure in hypertension patients after the intervention. The analysis of differences showed a significant difference in the average value of blood pressure reduction in those who followed the DASH diet. This study is in line with previous studies where the DASH Diet is quite effective in controlling high blood pressure (hypertension). Conclusion: The DASH Diet is a diet that has been recommended by WHO as a diet to control hypertension and has been proven to significantly lower blood pressure.